Human services in contemporary America - Burger, William, 1949- (Belmont, CA : Brooks/Cole, Cengage Learning, 2014)
'The content provides a general introduction to the field of human services and is designed for introductory college courses in human services, mental-health technology, social work, community mental health, and other human services programs.'--P. xviii.
Includes bibliographical references and indexes.
Keywords: Human services -- United States; Human services -- Vocational guidance -- United States; United States -- Social policy -- 1993-